A pathological condition in elephant dentition - Ian Parker (Pachyderm)
Growth of molars in the African elephant (Loxodonta africana) is redescribed as background for a pathological dental condition reported from four elephants in Kenya, one in Zimbabwe (where other cases have been seen) and 84 in Uganda. Apparently chronic in two Uganda populations, it was found in both sexes of all ages. Speculatively attributed to the malnutrition described by Laws, in the individual the condition seems temporary with evidence of recovery. While of veterinary interest, at a population level the condition may warn of nutritional deficiency with management implication.